PENERIMAAN PENONTON MENGENAI PERAN GENDER PADA KARAKTER PEREMPUAN DALAM FILM BUMI MANUSIA - Fajar Junaedi; Nabila Hilma Mujahidah (Universitas Bunda Mulia, 2021)
This research is an reception analysis from Stuart Hall theory developed by David Morley. The research aims to find out how the audience in accepting and interpreting gender roles in women in Bumi Manusia film through in depth interviews and Focus Group Discussion (FGD) with seven informants. Informants came from Klub DIY Menonton, Montase Film, Feminis Yogya, Yogyakarta Hijrah, LDK Jama’ah Shalahuddin, Rumah Baca Komunitas, dan Himpunan Mahasiswa Islam (HMI) Tunas Bangsa. Bumi Manusia is a historical genre film directed by Hanung Bramantyo. The film tells the suffering of the natives and the suffering of women in the suppression of patriarchal culture. The results of the study prove the concept of active audiences in interpreting media messages. The researcher found the encoding-decoding is in dominant-hegemonic position. The informant agree that woman is in second position in society and law.